Grid integration techniques with wind power plants - Ong, Tee Wee. (2010)
With the rapid increase in demand for renewable energy to provide solutions for environmental concerns and decreasing natural resources, Wind Turbine Systems have been greatly called upon to meet this demand. However, materializing the Wind Turbine Power Plant has its own restrictions and limitations such as transportation and installation of electrical equipment, connection to electrical grid, maintenance and uneven wind supply throughout the day on mainland and offshore islands. In this report, a concept is proposed using Static Synchronous Series Compensator (SSSC) to inject into the Wind Turbine System to increase the output power supply and improve the power factor. This is done by injecting capacitive reactive power to reduce the Wind Turbine and line inductances. The SSSC comprises of a dc source powered full-bridge IGBT-inverter (SSSC Inverter) connected to the Wind Turbine System through a coupling transformer. Closed-loop controllers are designed for both the DC-AC Inverter (in main circuit) and SSSC Inverter to maintain the output voltage at a stable level for the power grid. This concept is tested by MATLAB-PLECS simulation programme and experimented using scaled hardware devices. The detailed explanation and results are presented in this report. This report also records the different tasks completed to meet the requirements for my Final Year Project as part of my Bachelor studies in Nanyang Technological University.